Validation of micro-computed tomography for occlusal caries detection: an in vitro study - Gökhan ÖZKAN; Aydan KANLI; Nurdan Meserret BAŞEREN; Umut ARSLAN; İlkan TATAR (Sociedade Brasileira de Pesquisa Odontológica, 2015)
Conventional methods of caries detection, including the gold standard of histological examination, have certain disadvantages that must be addressed prior to validating any other diagnostic technique-current or new. Here we evaluated the validity of micro-computed tomography (micro-CT) as an alternative gold-standard technique for caries detection. Sixty teeth with suspected occlusal caries were chosen from a pool of teeth extracted for orthodontic, periodontal, or surgical reasons. Identical reference points were marked on photographs taken for teeth and were used to evaluate each method. Dimensions of caries were assessed by two calibrated examiners using the ICDAS-II visual examination system, bitewing radiographs, and micro-CT. The teeth included in the study were selected randomly from solution before all measurements. For micro-CT, the device was set to 50 kV, 800 µA, pixel size 15 µm (at 1024 × 1024 resolution), and 1° rotation step. NRecon software (SkyScan) was used to obtain reconstructed images. For each diagnostic method, results were compared with histology results using the McNemar test. Receiver operator characteristic (ROC) analysis was also performed for each method (Z-test; p < 0.05). Besides showing a high correlation with histology results, micro-CT yielded the greatest values at the D3 threshold; moreover, accuracy and area under the ROC curve (AUC) values were greatest at the D1threshold. Our results indicate that micro-CT performs as well as or better than histological examination for the purpose of comparing methods for caries detection.